A Theory on the Impact of Copper and Micronutrients Against COVID-19 in Humans - A. Connor DAOM PGDip AMP EHP-C, Caitlin (International Journal of Infection Prevention, 2021)
Copper (Cu) has a strong impact on the function of the immune system through several different pathways. These impacts include helping the function of monocytes, neutrophils, and macrophages, and enhancing Natural Killer cells’ activities. Cu also has a role in antimicrobial properties and inflammatory response. It is also important for IL-2 production and response, which is a component of adaptive immune cells. Additionally, Cu has multiple roles in both proliferation and differentiation of T cells and is involved in the production of antibodies. Cu deficiency can even lead to "increased viral virulence"1. Copper has a long history of use in medicine, and has continued to be used for purification of water, including use in hospitals to prevent legionnaires disease. The CDC pre released information on a study completed in March 2020 on the lifespan of COVID-19 on different surfaces which included its lifespan on copper, where it was completely dead within 4 hours. In addition, "Several reports demonstrated that Cu deficiency weakens the human immune response" 2. Given the multiple avenues of impact, it has been suggested that Cu supplementation, within recommended levels, be given to individuals who are low in Cu to help them fight off COVID-19. It is also possible that Cu supplementation, within recommended levels, may help prevent COVID-19 infection, or help individuals who are not low in Cu to fight off COVID-19 infection. However, dosage would have to be carefully managed, as excess levels of Cu can lead to both neurodegenerative and neurodevelopmental diseases.
Keywords: COVID-19; SARS COV 2; Copper Files